67% of US credit card holders would pay extra for biometric security. (April 2017) - Unknown
Abstract : 80% of US credit card holders are seriously concerned about credit card and identity theft and 67% would pay extra for biometric security. That is according to research commissioned by SmartMetric of credit card holders in the US.